Quality of life of low back pain patients following self back care intervention - Rahman Robin, M. Ashikur; Ziaul Islam, M.; ., Akhiruzzaman; Morshed, M. Shariar (International Journal Of Community Medicine And Public Health, 2018)
Background: Low back pain is the major health problem which is experienced by people at any stage of lifetime. The study was conducted to assess the quality of life (QOL) of low back pain (LBP) patients following self back care intervention. Methods: A quasi-experimental study was carried out among adult (18-59 years) LBP patients. A self-back care intervention was applied to compare QOL of low back pain patients before and after intervention by using SF-20 scale. Results: The study showed that mean (±SD) age was 37.41 (±10.63) years and majority (52.7%) of the LBP patients was female. The study revealed that LBP was common among married housewives and mean duration of LBP was 3.59 (±3.52) years. Majority (55.4%) of the patients had poor QOL before intervention but after self back care intervention most (83.9%) of them had average QOL. Mean (±SD) score of QOL after intervention (57.83±8.74) was significantly (t, p˂0.001) higher to before intervention (49.30±11.31). It was also found that mean QOL score with long duration of LBP (50.526±6.844) was significantly (ANOVA, p˂0.001) lower than QOL with short duration of LBP (65.137±9.538). The study also found that when severity of pain increased, mean QOL score significantly (ANOVA, p˂0.001) decreased after intervention. Mean QOL score significantly correlated with duration of LBP (r=-0.382 p˂0.01). Linear regression of mean QOL and duration of LBP before intervention were R2=0.146 and after intervention were R2=0.214. Conclusions: Self back care is an effective intervention to improve QOL of LBP patients. So encouraging health education measures regarding self back care.